Critical conditions of forced ignition in Ni-Al, Ti-Al powder systems under solid-phase synthesis - Filimonov, Valeriy Yu (Combustion and flame)
A theoretical study of the critical conditions of forced solid-phase ignition in Ti-Al, Ni-Al systems was carried out. Based on the analysis of the non-stationary diffusion equation with moving boundaries, the critical powers of the heating source and the corresponding critical temperatures were determined during the formation of NiAl, TiAl3 intermetallic compounds using the state diagrams of these binary systems. The diffusion activation energies, frequency factors, particle sizes, and heat removal conditions were considered as variable parameters. The diagrams of critical parameters which relate the corresponding specific heating powers with the indicated values were constructed. It has been established that for the same values of the parameters and under identical synthesis conditions, the critical temperatures in these systems differ by more than one hundred degrees. The latter is associated with a significant difference in the width of the solubility region for the corresponding compounds of the composition NiAl, TiAl3. The performed analysis allows separating the modes of isothermal sintering and thermal explosion which makes it possible to control the thermal and diffusion modes of synthesis. The comparison of the calculation results with the experimental data showed their satisfactory agreement.